Penentuan Rute Pendistribusian Gas LPG Menggunakan Algoritma Prim dengan Optimalisasi melalui Pergantian Sisi - Syamsuddin Mas'ud (Universitas Cokroaminoto Palopo, 2024)
This research examines the determination of LPG gas distribution routes. The study is conducted on data collected by Elia Resita Ningrum in her research titled